1998
DOI: 10.1149/1.1838754
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Electroless Cobalt Coatings for Microencapsulation of Hydrogen Storage Alloys

Abstract: LaNi4 275n,24 alloy was microencapsulated with cobalt by electroless deposition from an alkaline hypophosphite bath. Discharge curves of the encapsulated alloy indicate an additional contribution to the capacity arising from the cobalt on the surface. Studies on cobalt thin films reveal the presence of adsorbed hydrogen in cobalt. The amount of hydrogen adsorbed was observed to increase with time of cathodic polarization and to reach a maximum. Polarization techniques have been used to characterize the cobalt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…This agrees with the results shown by McKeown et al 9 Similar behavior ͑increased discharge currents at lower scan rates͒ has also been observed for metal hydride electrodes where the transport of hydrogen within the particle is rate limiting. 16 Charge-discharge studies.-The capacitance obtained from CVs was confirmed by chronopotentiometric studies at various applied currents. Figure 8A presents the galvanostatic charge-discharge curves for the RuO 2 -carbon composite heated at 100°C.…”
mentioning
confidence: 83%
“…This agrees with the results shown by McKeown et al 9 Similar behavior ͑increased discharge currents at lower scan rates͒ has also been observed for metal hydride electrodes where the transport of hydrogen within the particle is rate limiting. 16 Charge-discharge studies.-The capacitance obtained from CVs was confirmed by chronopotentiometric studies at various applied currents. Figure 8A presents the galvanostatic charge-discharge curves for the RuO 2 -carbon composite heated at 100°C.…”
mentioning
confidence: 83%
“…This may relate to the dissolution and precipitation of Co(OH) 2 in alkaline electrolyte. Haran et al [24] mentioned that the Co(OH) 2 could be oxidized to HCoO 2 − in alkaline solution, which could be subsequently precipitated into Co(OH) 2 in the solution. It is fortunate that the formed HCoO 2 − is only fractional [24].…”
Section: Charge and Discharge Propertiesmentioning
confidence: 99%
“…Haran et al [24] mentioned that the Co(OH) 2 could be oxidized to HCoO 2 − in alkaline solution, which could be subsequently precipitated into Co(OH) 2 in the solution. It is fortunate that the formed HCoO 2 − is only fractional [24]. We found that the KOH solution exhibits a sky-blue color after the first cycle, followed by an apparent light brown color on the inner surface of the glass pipe of the half-cell.…”
Section: Charge and Discharge Propertiesmentioning
confidence: 99%
“…Equation 15 can be used to modify Eq. 12 [16] The boundary condition at x ϭ 1 is not homogeneous and suggests a transformation of the form 15 …”
Section: Mathematical Model For the Discharge Processmentioning
confidence: 99%